The new global trading order : the evolving state and the future of trade - Patterson, Dennis M. (Dennis Michael), 1955-; Afilalo, Ari. (Cambridge : Cambridge University Press, 2010)
In this book, the authors propose a new trade norm - the enablement of global economic opportunity - and a new institution - the Trade Council - to overhaul the global trading order.
Includes bibliographical references and index.
nif 26/04/13
Loans
Keywords: International trade; International economic relations; International finance